2019
DOI: 10.1101/847160
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strand asymmetry influences mismatch resolution during single-strand annealing

Abstract: Biases of DNA repair can shape the nucleotide landscape of genomes at evolutionary timescales. However, such biases have not yet been measured in chromatin for lack of technologies. Here we develop a genome-wide assay whereby the same DNA lesion is repaired in different chromatin contexts. We insert thousands of barcoded transposons carrying a reporter of DNA mismatch repair in the genome of mouse embryonic stem cells. Upon inducing a double-strand break between tandem repeats, a mismatch is generated when the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
2
2
0
Order By: Relevance
“…This work complements a recent study that used a multiplexed reporter for DNA mismatch repair, which did not reveal significant effects of chromatin context on the repair outcome ( Pokusaeva et al., 2019 ). Another multiplexed integrated reporter study also found evidence that genomic location can affect Cas9 editing efficiency ( Gisler et al., 2019 ), but these results were more difficult to interpret because the reporter sequence itself was not transcriptionally inert.…”
Section: Discussionsupporting
confidence: 80%
“…This work complements a recent study that used a multiplexed reporter for DNA mismatch repair, which did not reveal significant effects of chromatin context on the repair outcome ( Pokusaeva et al., 2019 ). Another multiplexed integrated reporter study also found evidence that genomic location can affect Cas9 editing efficiency ( Gisler et al., 2019 ), but these results were more difficult to interpret because the reporter sequence itself was not transcriptionally inert.…”
Section: Discussionsupporting
confidence: 80%
“…This work complements a recent study that employed a multiplexed reporter for DNA mismatch repair, which did not find significant effects of chromatin context on the repair outcome (Pokusaeva et al, 2019). Another multiplexed integrated reporter study also found evidence that genomic location can affect Cas9 editing efficiency (Gisler et al, 2019), but these results were more difficult to interpret because the reporter sequence itself was not transcriptionally inert.…”
Section: Discussionsupporting
confidence: 67%
“…It will be interesting to apply DSB-TRIP with other CRISPR endonucleases such as Cas12a (Zetsche et al, 2015) or rare-cutter restriction enzymes such as I-SceI (Niu et al, 2008) or AsiSI (Iacovoni et al, 2010) (Figure 2A, bottom). I-SceI was successfully applied to study Single Strand Annealing in a TRIP assay (Pokusaeva et al, 2021). Another option are transcription activator-like effector nucleases (TALENs) (Boch et al, 2009;Gaj et al, 2013;Moscou and Bogdanove, 2009), especially since it was found that these nucleases are more efficient in heterochromatin, compared to Cas9 (Jain et al, 2021).…”
Section: Additional Applications Of Dsb-tripmentioning
confidence: 99%
“…Several studies have demonstrated that the local chromatin state is one of the factors that influences which pathway is preferentially used to repair a DSB. These studies used methods ranging from using single imprinted endogenous loci (Kallimasioti-Pazi et al, 2018), single transgenic loci (Lemaitre et al, 2014), hundreds of endogenous loci (Iacovoni et al, 2010;Massip et al, 2010;Aymard et al, 2014) to thousands of integrated reporters as presented here (Gisler et al, 2019;Pokusaeva et al, 2021;Schep et al, 2021). All these studies rely on endonucleases creating a DSB at a defined locus in the genome, targeting either a definite sequence (e.g., restriction enzymes) (Iacovoni et al, 2010) or a user-defined one (Kallimasioti-Pazi et al, 2018;van Overbeek et al, 2016;Chakrabarti et al, 2019) [e.g., with CRISPR/Cas9 (Jinek et al, 2012;Cong et al, 2013;Jinek et al, 2013;Mali et al, 2013)].…”
Section: Introductionmentioning
confidence: 99%